(untitled) (Clinics, 2007)
INTRODUCTION: The time-compressed speech test has existed since the 1970s. It is sensitive for evaluating auditory closure. However, it is not used in Brazil because until recently, it had not been developed in Portuguese. PURPOSE: To develop a compressed speech test in Portuguese, to apply it to normal-hearing adults, and to verify which of the compressed lists (50%, 60%, or 70%) is the most appropriate to be part of a set of auditory processing tests. METHODS: 144 normal-hearing adults, distributed homogeneously between both genders, were assessed. The compressed speech tests were applied using monosyllables and disyllables according to 8 previously established sequences, and the results were compared with respect to the initial ear, to the order of presentation, and to the kind of test. RESULTS: There were no significant differences between ears. The 50%, 60% and 70% presentation order produced a better average of correct responses than the 70%, 60% and 50% one. There was a significant difference (P